The Impact of Emotional Work And Work Stress On The Work-Life Balance of Employees In Private Banking Subsidiaries - Arya Permana, Dwi; Sulaeman , Faqih; Suzana , Anna; Rudianto , Yodi (Journal Research of Social Science, Economics, and Management, 2024)
Emotional labor is an integral part of many jobs, especially those that involve interactions with other people. Employees who perform emotional labor are required to manage their emotions and display emotions that are appropriate to the demands of the job. This research aims to analyze the impact of emotional labor on employees’ work-life balance. This research uses quantitative research. The data collection technique used was a questionnaire. The data that has been collected is then analyzed in the validity test, reliability test, normality test, and regression test. The results showed that emotional labor and work stress affect employees’ work-life balance. Employees who do emotional labor and work stress are more likely to experience fatigue, and difficulty separating work life and personal life. Companies need to overcome these negative impacts, including with various social support company policies that support work-life balance can help employees overcome the negative impacts of emotional labor and work stress.